The Thai Anesthesia Incident Monitoring Study (Thai AIMS) of desaturation: An analysis of 1,996 incident reports - Sirilak Suksompong (2018)
Background and Rationale: The present study is a part of the Multicentered Study of Model of Anesthesia related Adverse Events in Thailand by Incident Report (The Thai Anesthesia Incident Monitoring Study or Thai AIMS). The objective of the present study was to determine the frequency distribution, outcomes, contributory factors, and factors minimizing incident. Material and Method: The present study is a prospective descriptive research design. The authors extracted relevant data from the incident reports on oxygen desaturation from the Thai AIMS database and analyzed during the study period between January and June 2007. Results: From the relevant 445 incidents, most of the incidents (89%) occurred in patients receiving general anesthesia. The incidence in patients receiving regional anesthesia was 4.0%. The events mostly occurred in patients aged between 16-65 years (52.8%). Most of the events (76%) took place in the operating theater during the induction period (30.1%). More than 81% of the patients experienced severe oxygen desaturation (SpO2 < 85%). There were 55 patients (12.4%) who had unplanned ICU admission and 2 patients (0.4%) who had unplanned hospital admission. Factors that may relate to the incident involve combined factors (50.8%). Anesthetic factors were found to involve 38.4% of incidents. The common contributing factors that might lead to the incidents were inexperienced (57.5%), inappropriate decision (56.2%), and haste (23.8%). For factors minimizing incident, the important factors were vigilance (86.3%), experienced in that tropic (71.2%), and experienced assistance (54.8%). Quality assurance activity was the most common suggestive corrective strategy (79.1%). The others were improvement of supervision (47.2%) and guideline practice (46.5%). Conclusion: To lower the incidence of oxygen desaturation, the anesthesia personnel has to improve the anesthesia services by quality assurance activity, improvement of supervision, clinical practice guidelines, and additional training.